Comparative analysis of decametre 'drift pair' bursts observed in 2002 and 2015 - Volvach, Ya.S.; Stanislavsky, A.A.; Konovalenko, A.A.; Koval, A.A.; Dorovskyy, V.V. (Advances in Astronomy and Space Physics, 2016)
We report about new observations of solar "drift pair" (DP) bursts by means of the UTR-2 radio telescope at frequencies 10-30 MHz. Our experimental data include both "forward" and "reverse" bursts with high frequency and time resolution. The records of 301 bursts, observed in 10 12 July of 2015, are investigated. The main properties of these bursts (frequency bandwidth, central frequency and others) have been analysed. In this report our main attention is paid to the comparison of our observations with the similar observations of decametre DPs performed earlier during 13-15 July of 2002 in the same frequency range. Common features of DPs in the two different pieces of data samples have been found. This may indicate the possible presence of stability in the frequency-time properties of decametre DPs from one cycle of solar activity to another.